The Management Of Micro and Small Business In Bengkulu - Djamil, MM., Prof. Dr. H. Masydzulhak (Jurnal Manajemen, 2018)
Regional autonomy essentially is the central government policy to quicken the development and service to public in region. Nevertheless, there are still many constraints and obstacles for development in some region. This might be caused by the incapability of Government in interpreting the meaning of regional autonomy. Small and medium industry (UKM) have been proven been able to survive in economic crisis in the year 1997 / 1998. The time has come for Government to make cooperation and give bigger opportunity to grow UKM business. Scale number of (UKM) in Bengkulu province can become economic bases of area either for economic regional contribution or PDRB and labor absorption. The policy of small and middle business management is to effectively arrange and efficiency applied economic resource, with considering regional carrying capacity of coastal area.